Nematic Phase Transitions in an Assembly of Molecules with a Bent Core - Hosino, Masahito (European Journal of Applied Sciences, 2025)
Approximately 20 years ago, Hosino and Nakano [1] investigated the phase transitions in an assembly of biaxial molecules that interact via dispersion forces, discovering the existence of one uniaxial and two biaxial nematic phases and disconematic phase in the assembly. Follow-up studies obtained valuable results on the phase transitions in an assembly of biaxial molecules with hard cores [2], chirality [3, 4], and flexibility [5] based on the initially proposed method [1]. In this study, the phase transitions in the assembly of molecules with a bent core were investigated using the same method, demonstrating the occurrence of sequence of transitions between various nematic phases in the system.